Matrix Gla protein maintains normal and malignant hematopoietic progenitor cells by interacting with bone morphogenetic protein-4. Issue 4 (April 2020) - Kuronuma, Kana; Yokoi, Aya; Fukuoka, Tomoya; Miyata, Muneaki; Maekawa, Akio; Tanaka, Satowa; Matsubara, Leo; Goto, Chie; Matsuo, Miki; Han, Hao-Wei; Tsuruta, Mai; Murata, Haruka; et al.
Abstract: Matrix Gla protein (MGP), a modulator of the BMP-SMAD signals, inhibits arterial calcification in a Glu γ-carboxylation dependent manner but the role of MGP highly expressed in a subset of bone marrow (BM) mesenchymal stem/stromal cells is unknown. Here we provide evidence that MGP might be a niche factor for both normal and malignant myelopoiesis. When mouse BM hematopoietic cells were cocultured with mitomycin C-treated BM stromal cells in the presence of anti-MGP antibody, growth of hematopoietic cells was reduced by half, and maintenance of long-term culture-initiating cells (LTC-ICs) was profoundly attenuated. Antibody-mediated blockage of MGP also inhibited growth (by a fifth) and cobblestone formation (by half) of stroma-dependent MB-1 myeloblastoma cells. MGP was undetectable in normal hematopoietic cells but was expressed in various mesenchymal cells and was aberrantly high in MB-1 cells. MGP and bone morphogenetic protein (BMP)-4 were co-induced in stromal cells cocultured with both normal hematopoietic cells and MB-1 myeloblastoma cells in an oscillating several days-periodic manner. BMP-2 was also induced in stromal cells cocultured with normal hematopoietic cells but was barely expressed when cocultured with MB-1 cells. GST-pulldown and luciferase reporter assays showed that uncarboxylated MGP interacted with BMP-4 and that anti-MGP antibody abolished this interaction. LDN-193189, a selective BMP signaling inhibitor, inhibited growth and cobblestone formation of MB-1 cells. The addition of warfarin, a selective inhibitor of vitamin K-dependent Glu γ-carboxylation, did not affect MB-1 cell growth, suggesting that uncarboxylated MGP has a biological effect in niche. These results indicate that MGP may maintain normal and malignant hematopoietic progenitor cells, possibly by modulating BMP signals independently of Glu γ-carboxylation. Aberrant MGP by leukemic cells and selective induction of BMP-4 relative to BMP-2 in stromal cells might specify malignant niche. Abstract : Biochemistry; Cancer research; Cell biology; Molecular biology; Physiology; Stem cells research; Biomolecules; Molecular dynamics; Hematological system; Oncology; Matrix Gla protein (MGP), Bone morphogenetic protein-4 (BMP-4), BMP-2, Hematopoietic niche, Mediator transcriptional coregulatory complex.